Revitalizing Ismail Raji Al-Faruqi’s Axiology of Tawhid as a Foundation for Social Media Ethics in the Digital Era - Fatiha Amila Sholihah; Agus Wahyu Triatmo (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2026)
Rapid technological advancement has transformed social media from a mere communication tool into an integral part of everyday life. However, this transformation has not been accompanied by users’ moral maturity and ethical readiness, resulting in the widespread occurrence of hate speech, cyberbullying, hoaxes, disinformation, and other forms of unethical online behavior. Although formal regulations, such as Indonesia’s Electronic Information and Transactions Law (ITE Law), provide legal sanctions for digital misconduct, they have proven insufficient to cultivate users’ internal moral responsibility because they lack a strong spiritual foundation. This study aims to formulate a spiritually grounded yet practically applicable framework for social media ethics based on Ismail Raji Al-Faruqi’s axiology of tawhid. Employing a qualitative library research approach, this study analyzes Al-Faruqi’s concept of tawhid through content analysis and contextualizes it within contemporary challenges of digital ethics. The findings reveal five ethical principles for responsible social media engagement: (1) spiritual responsibility derived from the Unity of God; (2) the utilization of social media for the common good derived from the Unity of Creation; (3) the application of tabayyun (verification) to maintain information integrity derived from the Unity of Truth and Knowledge; (4) the alignment of moral consistency between real and virtual life derived from the Unity of Life; and (5) respect for human dignity and equality derived from the Unity of Humanity. These findings demonstrate that AlFaruqi’s axiology of tawhid provides a comprehensive ethical foundation that integrates spiritual values with responsible digital citizenship, thereby offering an alternative framework for addressing contemporary moral challenges in social media.